THE SPECTACULARIZATION OF A SCHOOL EVENT (Fiep Bulletin - online, 2014)
Abstract: In Ponta Grossa/PR, it's appropriate to note the sports competitions not only as a recreation and learning vehicle, but also as publicity one. This research parts from the perception that to major number of public and private learning institutions in the city have worked with Physics Education aiming the Municipal Student Games (JEM). Trying to understand this phenomenon, the present paper has the aim of doing a JEM's historical research. This research implies in collect qualitative data, that is, goals, an appropriation of the goals in its creation, and quantitative, referring to the school and students adhesion to this event. These data have been rescued from the reports of the eighteenth editions of this event and through interviews given by people involved in its creation. Some preliminary evaluations show that JEM was created to fulfill a gap with the extinction of another competition called OLIJUP. Recreational and educational aspects characterized this competition. JEM, when created, also followed these prerogatives. In a preliminary conclusion, it can be highlighted that the possible recipe, or at least one of the ingredients for JEM's success was the fact of it presents itself as an effective mediator in the educative processes and to have a commitment with the recreation. But, the latter and overpowering growth was the result of its turning into an spectacle.
Keywords: school event; marketing; spectacularization